SAT0521 Lesinurad, an Inhibitor of the Uric Acid Transporter URAT1 and A Potential Therapy for Gout, Requires URAT1 Phenylalanine 365 for High Affinity Inhibition. (10th June 2014) - Tan, P.K.; Hyndman, D.; Miner, J.N.
Abstract : Background: In most patients, gout is caused by inefficient excretion of uric acid, resulting in hyperuricemia and the formation of crystal deposits of uric acid. The renal uric acid transporter URAT1 ( SLC22A12 ) is important for regulating serum uric acid levels. Lesinurad is a selective uric acid reabsorption inhibitor (SURI) that inhibits URAT1 and is currently under Phase 3 clinical evaluation in patients with gout. Objectives: To define the molecular interaction of lesinurad with URAT1. Methods: HEK-293T cells transiently expressing chimeric URAT1 mutants were used to measure cell-based uric acid transport activity in the presence of lesinurad and other URAT1 inhibitors. A binding assay was also developed using membrane preparations from transfected cells and radiolabeled RDEA3170, a high-affinity URAT1 inhibitor also in development for gout. Binding was measured after incubation with lesinurad and other URAT1 inhibitors. Results: Lesinurad inhibits the uric acid transport activity of human URAT1 (hURAT1) at a 20-fold higher potency compared to rat URAT1 (rURAT1), with IC50 's of 3.36 and 74.84 μM, respectively. Chimeras containing portions of the rat and human genes identified a single residue, hURAT1 phenylalanine 365, located within transmembrane segment 7, as crucial for the higher affinity interaction with lesinurad. Among the known URAT1 orthologs, Phe365 occurs only in humans, apes, and certain monkeys, whereas a tyrosine residue occurs in all other animals, including the rat. In particular, the single chimeric point mutant hURAT1-Tyr365 shows a significantly reduced sensitivity for inhibition by lesinurad (IC50 =47.76 μM) compared to wild type hURAT1, while the converse point mutant rURAT1-Phe365 displays a significantly enhanced sensitivity (IC50 =6.82 μM) compared to wild type rURAT1. Phe365 is also important for the interaction between hURAT1 and other commercially available URAT1 inhibitors benzbromarone, probenecid, and sulfinpyrazone. Lesinurad, as well as other URAT1 inhibitors, all bind competitively to the same site on URAT1. Consistent with in vitro inhibition of URAT1, lesinurad treatment results in an increased fractional excretion of uric acid and a decrease in serum uric acid in clinical trials. Conclusions: Lesinurad inhibits hURAT1 through an interaction that involves a critical residue, Phe365. The gain-of-function phenotype of rURAT1-Phe365 suggests that Phe365 directly binds to lesinurad. Phe365 is also important for the interaction with other URAT1 inhibitors, and this residue likely forms part of an inhibitor binding site within the transporter channel of URAT1. Acknowledgements: Research sponsored by Ardea Biosciences/AstraZeneca. Disclosure of Interest: P. Tan Employee of: Ardea Biosciences, Inc, D. Hyndman Employee of: Ardea Biosciences, Inc, J. Miner Employee of: Ardea Biosciences, Inc DOI: 10.1136/annrheumdis-2014-eular.4476